The impact of food choices on human and animal rights protection and environmental sustainability - Raquel Guiné; Paula Correia; Manuela Ferreira; Monica Tarcea; Elena Bartkiene; Elena Vittadini (Instituto Politécnico de Viseu, 2020)
Introduction: People's food choices are of the utmost importance to regulate markets and the food chain towards the global goal of sustainability.  Objectives: The objective of this work was to evaluate to what extent some aspects linked to sustainability in the food chain influence people's food choices, specifically in the domains of packaging, food surplus, transportation and human or animal welfare.  Methods: This is a cross-sectional study involving 3183 people from Portugal, Italy, Lithuania and Romania, who participated in this questionnaire survey between January and June 2018.  Results: People tend to condition their food choices in view of contributing for a more sustainable food chain with respect for environment, humans and animals. The areas in which this behaviour is stronger include avoiding food waste at home (80% of participants), preference for local foods (60%), sustainable food growing, preparation or packaging (66%). The respect for animal rights is very important for 62% of the participants, but the respect for Human rights is a concern for just 32%. The results of statistical tests indicated that age, education, country, professional area and type of diet all significantly influenced people's choices regarding the sustainability of the food chain.  Conclusions: Although the results are indicative that people start to condition their eating behaviours also according to sustainability issues, it is a fact that there is still work to be done, since the adoption of these sustainable choices is still in a limited extent.